2020
DOI: 10.3389/fimmu.2020.572475
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Cytokine Inhibition Modulates Activation and Homing Receptors of Peripheral Memory B Cell Subsets in Rheumatoid Arthritis Patients

Abstract: Memory B cells have known to play an important role in the pathogenesis of rheumatoid arthritis (RA). With the emergence of B cell-targeted therapies, the modulation of memory B cells appears to be a key therapeutic target. Human peripheral memory B cells can be distinguished based on the phenotypic expression of CD27 and IgD, characterizing the three major B cell subpopulations: CD27+IgD+ pre-switch, CD27+IgD-post-switch, and CD27-IgD-double-negative memory B cells. We evaluated different memory cell populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
0
11
1
Order By: Relevance
“…However, contrary to current findings, another study conducted on the Pakistani population reported a positive association between rs361525 and OA development in the Pakistani population [40]. Like the findings of the current study, no positive association has been reported in the Chinese, Mexican, and Iraqi populations [40][41][42].…”
Section: Discussioncontrasting
confidence: 99%
“…However, contrary to current findings, another study conducted on the Pakistani population reported a positive association between rs361525 and OA development in the Pakistani population [40]. Like the findings of the current study, no positive association has been reported in the Chinese, Mexican, and Iraqi populations [40][41][42].…”
Section: Discussioncontrasting
confidence: 99%
“…RA causes pain, stiffness, and swelling joints, leading to loss of physical function, work disability, and decreased quality of life of patients [ 85 ]. Its pathogenesis is still unclear, but it is known that pro-inflammatory cytokines such as IL-6 and TNF are involved in joint inflammation and extra-articular manifestations [ 86 , 87 , 88 , 89 , 90 , 91 ].…”
Section: Mabs In Rheumatoid Arthritismentioning
confidence: 99%
“…Double negative (DN) B cells (CD19 + /CD27 − /IgD − ), although lacking CD27-expression, show somatic hypermutation of the B cell receptor and are, therefore, attributed to the memory compartment [18]. DN B cells play a pathogenic role in autoimmune diseases, as they are enhanced and activated in systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%